Static Loading Analysis of Chips Chopper Machine Design with Feeder Spring Addition - Agus Choirul Arifin; rahayu mekar bisono; Wida Rezika (International Journal of Science, Engineering, and Information Technology, 2022)
This study aims to design an assorted chip chopper that can cut various kinds of raw materials for making chips such as cassava, sweet potato, taro and so on. Product design is important to carry out the production process. Product design helps estimate and analyze requirements with more accurate results than without doing this process. The design in this study was carried out using the Solidworks 2020 software. The dimensions of the machine obtained from the design results were 330 mm long, 330 mm wide, and 285 mm high with a mass of 1.59 kg. The novelty of the design that has been made is the addition of a feeding spring, so that the material input process is more stable and safer. Feeding springs can also improve the quality of the cut. In addition to making the design, a simulation of the calculation of the maximum von Mises value is also carried out with the aim of knowing the safety factor of the design that has been made. From the simulation results, the maximum von Mises Stress value of Force 1 is 1,470 MPa, and Force 2 is 9,846 MPa. This value is obtained from the provision of Force 1 32.49758 and Force 2 18.718. This value is far below the yield strength of the material (250 MPa) so it can be concluded that the design is safe to proceed to the production process.